Socio-Ecological Management of Drawdown Farming in Jatigede Embankment Dam (West Java, Indonesia) - Opan Suhendi Suwartapradja; Budiawati S. Iskandar; Johan Iskandar; Dede Mulyanto (Universitas Andalas, 2023)
The impact of the construction of the Jatigede dam caused at least 6,856 heads of households in 17 villages as affected people (Orang terkena dampak-OTD) must move to new area. They must develop adaptation strategies to make various efforts to obtain income to maintain their survival in new area. Among the efforts made by OTD of Jatigede, they have utilized drawdown area of Jatigede for cultivating various crops . The objective of the paper is to elucidate the socio-ecological strategy of OTD of Jatigede who reside in Maleber Hamlet, Wado Village, Sumedang District, in managing drawdown area. The method used in this study was a qualitative method with an ethnoagroecological approach. The results of the study showed that in an effort to adapt the OTD to a new environment, they have managed the drawdown area of Jatigede lake for cultivating various crops. Generally OTD have successfully managed the drawndown area by cultivating various crops. However, they have still difficulty maintained sustainable cultivating in the drawdown area due to climate changes and drought.